Preliminary design and development pesticides applicator in agriculture / Zazmir Sihi @ Ab Manaf - Sihi @ Ab Manaf, Zazmir (Faculty of Plantation and Agrotechnology, 2017)
In agriculture maintenance activity such as spraying is very important but the protection of the environment is very important. The objective of this study was to design a herbicides applicator that suitable for farmers to use in the agricultural sector. The herbicides applicator should be able of providing some easy ergonomic for farmers to handle it. In agricultural sector nowadays facing a major problem which is uncontrollable grow of weeds. Shortage of labor and inconvenient method need to be overcome. The consumption of pesticide is greatly increased over a period of time. The excessive use of herbicides in the nursery could decrease the growth of crops. Using weightage table, the conceptual design can be decided. After that, using software which is AutoCAD 2017 and Sketchup to design the pesticides applicator. The total cost of material per acres of this pesticides applicator is RM4.9/acre while CKS and Mist blower are RM4.30/acre and RM3.48/acre. Furthermore, the labor cost for CKS and Mist blower is RM3.80/acre and RM5.9/acre while the labor cost for this pesticides applicator is RM4.2/acre. The total cost producing this pesticides applicator is RM857.50. Moreover, the farmer does not need to carry the sprayer behind their back because this type of pesticides applicator only need to be push and will reduce the back pain and muscle cramp after spraying in the field. Able to reduce the consumption of chemical use because we can see the droplet of herbicides on crops compare to CDA. CDA’s droplet size is very small and easy to evaporate and also hard to see the mist. Uniform spray pattern because using a flat-fan nozzle.